The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1182/blood.v92.4.1350
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Regulation of T-Cell Death by CD28 Depending on Both Its Aggregation and T-Cell Receptor Triggering: A Role for Fas-FasL

Abstract: CD28 is a major coreceptor that regulates cell proliferation, anergy, and viability of T cells. The negative selection by T-cell receptor (TCR)-induced cell death of immature thymocytes as well as of activated human antigen-specific T-cell clone, requires a costimulatory signal that can be provided by CD28. Conversely, CD28-mediated signals increase expression of Bcl-XL, a survival gene, and promote survival of naive T cells cultured in the absence of antigen or costimulation. Because CD28 appears to both prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…In this study we demonstrate that TCR/CD3-restimulated mature activated human T cells can be rescued from apoptotic cell death through CD28 co-stimulation [38][39][40]42]. We have found that the CD28 co-stimulatory anti-apoptotic signal acts on multiple levels of TCR/CD3mediated induction of the CD95 pathway.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In this study we demonstrate that TCR/CD3-restimulated mature activated human T cells can be rescued from apoptotic cell death through CD28 co-stimulation [38][39][40]42]. We have found that the CD28 co-stimulatory anti-apoptotic signal acts on multiple levels of TCR/CD3mediated induction of the CD95 pathway.…”
Section: Discussionmentioning
confidence: 69%
“…Thereby, CD28 regulates cell proliferation, anergy and viability of T cells. CD28 appears to act both as a protector and an activator of apoptosis, depending on the stimulation conditions [38]. Several reports demonstrated that CD28-mediated signaling increases the expression of Bcl-x L and thereby promotes survival [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of CD28-mediated costimulation on CD95-triggered AICD was investigated only recently. It has been reported that under certain conditions, stimulation via CD28 prevents CD3-mediated induction of CD95L and, thus, AICD (94,115). The modulation of downstream signaling events in the CD95 pathway upon costimulation has been partially elucidated (94,116).…”
Section: Costimulation and Survivalmentioning
confidence: 99%
“…23 Independent treatment with these four cytokines can induce immunotolerance and prolong the survival of grafts to some extent. Collette et al 24 showed that blockade of the CD28:B7 costimulatory pathway can enhance T-cell sensitivity to CD95:CD95L-mediated apoptosis. Jay et al 25 revealed the synergistic effects of IL-10 and TGF-b in inducing CD4+ T cell-mediated, antigen-specific, low-level immune response.…”
Section: Introductionmentioning
confidence: 99%